2014
DOI: 10.5372/1905-7415.0804.319
|View full text |Cite
|
Sign up to set email alerts
|

RH genotypes among Malaysian blood donors

Abstract: Background: RH genotyping studies have been conducted mainly in people of Caucasian and African descent. There is limited information regarding the molecular basis for RH genotypes in Malaysia. Objectives: To investigate the prevalence and characteristics of RHCE genotypes among different ethnic groups in Malaysia. Methods: A total of 1014 whole blood samples were obtained from donors from 4 different ethnic groups (360 Malays, 434 Chinese, 164 Indians, and 56 others). All samples were phenotyped for C, c, D, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Rh system antigens had the highest mismatches (80.4%) among all 4 blood group systems in the present study with highest discrepancies found for E antigen (46/112 samples) as shown in Table 1. Prevalence E [14]. Similar findings were reported by Reid et al as one of E + samples had mixed field reaction in e typing and genotyped as RHE/RHE [16].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Rh system antigens had the highest mismatches (80.4%) among all 4 blood group systems in the present study with highest discrepancies found for E antigen (46/112 samples) as shown in Table 1. Prevalence E [14]. Similar findings were reported by Reid et al as one of E + samples had mixed field reaction in e typing and genotyped as RHE/RHE [16].…”
Section: Discussionsupporting
confidence: 86%
“…After completion of cross match procedures remaining EDTA samples were used for serological phenotyping of Rh, Kell, Duffy and Kidd system antigens and genotyping by molecule methods for the same antigens. Serological investigations were done by tube agglutination technique using conventional antisera for particular antigens from IMMUCOR, INC, U.S. Molecular investigation of Rh system antigens were carried out using allele specific PCR for RHCc [13,14] and RHEe [15] alleles and for investigating antigens of Kell, Duffy and Kidd antigens PCR-RFLP techniques were used [16]. Two ml of EDTA and 3 ml of clotted blood was taken from the recipients for extended grouping and cross matching just before next transfusion was due.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation